Bilateral synchronous UBE for unilateral laminotomy and bilateral decompression as a potentially effective minimally Invasive approach for two-level lumbar spinal stenosis - Yulin Zhao; Yingjun Guo; Xin Pan; Hao Li; Xianlei Gao; Haipeng Si; Wanlong Xu (Scientific Reports)
Currently, Unilateral biportal endoscopy is widely used in the surgical treatment of lumbar spinal stenosis. To investigate the feasibility of bilateral synchronous UBE to unilateral laminotomy and bilateral decompression(BS-UBE-ULBD) for treating two-level lumbar spinal stenosis (LSS). Sixty-four patients with two-level lumbar spinal stenosis (LSS) treated with BS-UBE-ULBD from October 2022 to January 2024 were retrospectively analyzed. All patients were treated with BS-UBE-ULBD. All 64 patients successfully underwent surgery, and the duration of surgery was 95–180 min, with an average of 119.92 ± 14.79 min. The average number of fluoroscopy was 3.02 ± 0.92. The average blood loss during the surgery was 73. 44 ± 36.70 ml. Postoperative lumbar CT showed that the spinal canal and bilateral nerve roots were fully decompressed. There were no postoperative complications, such as infection, severe nerve root injury, and lumbar instability. Complete follow-up data were obtained for all 64 cases. The VAS score of low back and leg pain and the ODI of lumbar function significantly (P < 0.05) improved at each follow-up time point. MacNab evaluation at 6 months after the surgery showed that the results were excellent in 48 cases, good in 14 cases, and fair in 2 cases. The excellent and good rate was 96. 88% (62/64). So BS-UBE-ULBD is a minimally invasive, highly effective, and safe procedure for 2-level LSS. Degenerative lumbar spinal stenosis (LSS) refers to clinical symptoms caused by the compression of the cauda equina, nerve root, and vascular complex. LSS can occur due to the abnormal shape and volume of the bony or fibrous structure after degenerative changes and the stenosis of the inner diameter of one or more lumens at a single level or multiple levels. It is a common cause of lumbago or lumbago and leg pain, which is common among middle-aged and elderly people1. LSS has become the most common cause of lumbar surgery among patients over 60 years of age2. However, traditional surgery necessitates extensive stripping of paraspinal muscles, which can easily lead to the ischemic injury of paraspinal muscles and atrophy after denervation. Therefore, traditional surgery may result in intractable back pain, stiffness, and discomfort after surgery3,4. Furthermore, as the posterior bone and soft tissue structures need to be extensively resected during the surgery, epidural scar and nerve compression are highly likely after the surgery. The high risk of general anesthesia cannot be ignored among elderly and weak patients2,5. Recently, with the rapid development of minimally invasive spine surgery, endoscopic surgery has been applied in the treatment of LSS6. Unilateral biportal endoscopy (UBE ) is more popular in treating LSS and is a more flexible operation, with small trauma, quick recovery, and a gentle learning curve. In addition, many studies have proven the good clinical efficacy of unilateral biportal endoscopy7. Multilevel spinal stenosis can be done simultaneously. Previously, the same operator decompressed multiple segments in turn8,9, but the operation lasted longer, and the corresponding problems, such as bleeding, high risk of anesthesia, and fluoroscopy frequency, increased. From October 2022 to June 2024, our hospital pioneered the use of Bilateral Synchronous UBE-unilateral Laminotomy and Bilateral Decompression (BS-UBE-ULBD) for two-level degenerative LSS. Sixty-four patients with two-segment LSS were treated with BS-UBE-ULBD, and the results were satisfactory.